The Scope of Nurturing Care in Early Childhood and Its Applications in Our Country - Elanur YOLAL KARİMOV; Gülbin GÖKÇAY (Namık Kemal Tıp Dergisi, 2025)
It is thought that supporting the early childhood period, which is of critical importance in terms of cognitive, social, emotional and physical development in children, with the components of the developmental care scope will increase the peace and welfare levels of future generations. In addition to the applications carried out in this context in our country, there is also a need for applications that we need to add to our health practice. The purpose of the review is to talk about the scope of nurturing care and nurturing care practices in our country in the light of current information and to offer suggestions to further develop the scope.